Dynamic arbitrage-free asset pricing with proportional transaction costs - Xiaotie Deng; Chunlei Xu; Shunming Zhang (The University of Western Ontario, Department of Economics, 2000)
This paper studies arbitrage-free conditions for multiperiod asset pricing in frictional financial markets with proportional transaction costs. We consider the Euclidean space for weakly arbitrage-free security markets and strongly arbitrage-free security markets, and establish the weakly arbitrage-free pricing theorem and the strongly arbitrage-free pricing theorem.
Keywords: 330; the first fundamental valuation theorems; frictional markets; weak arbitrage-freeness; strict arbitrage-freeness; arbitrage-free pricing theory